PENINDAKAN PENJAMIN WARGA NEGARA ASING DALAM KEBUTUHAN TERTENTU DALAM PERSPEKTIF MANAJEMEN PUBLIK PADA KANTOR IMIGRASI KELAS II TPI MIMIKA - Putri, Anisa Rizqi (Polteknik Imigrasi, 2024)
Abstract. The opportunities provided by Indonesia for foreign companies to invest and set up production offices in many vital areas attracts the interest of foreign workforces to come and stay. The government, thought the Immigration Offices as the work unit of Directorate General of Indonesian Immigration Ministry of Law and Human Rights has its duty to provide strict control over the misbehaving of the foreigners who may pose threats to local foreigners. The current problem is that in fact, foreign nationals who enters in order to work is supposed to be receiving its security insurance by the company who summons them as the prosecutor. This matter is regulated by article 63 Act Number 6 Year 2011 about Immigration. As regulated, this matter still has its problem on how to be a good social control and fulfilling the criteria of public management. This research’s purposes is to explain how the enforcement of such act must be generated and become one of the fulfilment indicator of the act of public management.